Chronic Idiopathic Neutrophilia in Two Twins - Miniero, Roberto; Mazza, Giuseppe Antonio; Altomare, Federica; Fusaro, Carla (Case Reports in Hematology, 2014)
Neutrophilia in adults refers to an alteration in the total number of blood neutrophils that is in excess of about 7500 cells/μL. This definition is restrictive in childhood as neutrophil count is age-dependent. Chronic Idiopathic Neutrophilia (CIN) refers to a condition that persists for many years in individuals who appear otherwise healthy. CIN is rarely mentioned in scientific literature and in academic books of hematology; only few words are dedicated to this topic. We report a case study of two twins with CIN followed from the first year of life to 24 years of age. To the best of our knowledge this is the first case report of two twins with CIN followed through a long period of time. We believe that our observation may contribute to better understand and characterize this hematologic abnormality.